Simbolisasi Mati Baghorai dalam Upacara Kematian di Minangkabau (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
This study aims to explore the meaning of the symbols contained in the mati baghorai in the Taluak community. This study used a qualitative method with an ethnographic type. 19 informants were selected by purposive sampling technique. This study found that mati baghorai is a funeral procession carried out by the Taluak community when a traditional leader dies. In its implementation, this tradition uses various tools, namely ghorai (corpse carrier), special clothes as a sign of traditional figures that are usually worn when alive, white cloth, umbrellas, and veils. The meaning that has been constructed from these tools is evidence of the greatness of traditional leaders, socialization of media heirs, hastening funerals, a form of sincerity for each tribe, each tribe protects each other, and leaders are rich people.